Circulating Brain-Derived Neurotrophic Factor, Antioxidant Enzymes Activities, and Mitochondrial DNA in Bipolar Disorder: An Exploratory Report - Wang, Dong; Li, Hong; Du, Xiangdong; Zhou, Jun; Yuan, Liu; Ren, Honghong; Yang, Xiaonan; Zhang, Guangya; Chen, Xiaogang (Frontiers in Psychiatry, 2020)
Abstract AIM: Accumulated evidence indicates that neurotrophin deregulations, oxidative stress injury and mitochondrial dysfunction have been involved in bipolar disorder (BD)；however, their real roles in BD are unclear. Investing the possible interaction between three systems is worthwhile understanding this complex process. Methods: We measured plasma Brain-derived neurotrophic factor (BDNF) level, leukocytes mitochondrial DNA copy number (mtDNAcn), and activity of antioxidant enzymes in BD patients (n = 97) and healthy controls (n = 31). Analysis of variance and linear regression analyses were performed to explore the interaction between mtDNAcn, antioxidant enzymes and BDNF. Results: Compared with healthy controls, there were significant decreases of glutathione peroxidase activity, BDNF levels and mtDNA content, significant increases of manganese superoxide dismutase (MnSOD) activity among BD patients (all p < 0.05). Regression analysis showed MnSOD activity had a moderate effect on BDNF, (beta = 0.23, t = 8.5, p = 0.001). Copper zinc SOD and total SOD activity were significantly correlated with Hamilton Depression Scale scores in depressive patients (r = -0.38, p = 0.013; r = -0.35, p = 0.022). Unexpectedly, we observed no significant correlation between mtDNA content and BDNF in BD patients (p > 0.05). Conclusion: The findings coincide with our hypothesis that abnormal antioxidant enzymes, mtDNAcn and peripheral BDNF may be involved in the course of BD. There were significant correlations between peripheral BDNF, antioxidant enzyme activities and mtDNAcn, suggesting that oxidative stress, mitochondrial function and BDNF may influence each other in BD.